Characterization of the reversible photoinduced optical changes in Sb-based glasses - Nalin, Marcelo [UNESP]; Poirier, G.; Ribeiro, Sidney José Lima [UNESP]; Messaddeq, Younes [UNESP]; Carvalho, E. J.; Cescato, L. (Elsevier B.V., 2006)
Changes occurring in absorption coefficients when glasses in the SbPO4-WO3 binary system were irradiated by light, at the edge of the absorption band, were measured in real time. These glasses present good thermal and optical properties and photoinduced changes in the absorption coefficients are reversible by heat treatment around 150 degrees C. Subsequent recording/erasing cycles could be made without sample degradation. The sensitivity of the induced optical changes was studied for different wavelengths, light powers and energy of light dose exposures, and for different compositions of the glasses. The changes in the absorption coefficients of the glass samples were accompanied by a color change from yellow to blue, and were also characterized by visible spectroscopy. The color changes occurred through the entire volume of the glass (similar to 2 mm thickness) for the Ar-ion laser lines at the edge of the absorption band. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: photochromic glasses; optical constants measurements; antimony